2022
DOI: 10.3389/fcimb.2022.934671
|View full text |Cite
|
Sign up to set email alerts
|

Gearing up for battle: Harnessing adaptive T cell immunity against gram-negative pneumonia

Abstract: Pneumonia is one of the leading causes of morbidity and mortality worldwide and Gram-negative bacteria are a major cause of severe pneumonia. Despite advances in diagnosis and treatment, the rise of multidrug-resistant organisms and hypervirulent strains demonstrates that there will continue to be challenges with traditional treatment strategies using antibiotics. Hence, an alternative approach is to focus on the disease tolerance components that mediate immune resistance and enhance tissue resilience. Adaptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Successful pulmonary immune responses to acute infection coordinate innate and adaptive immune events that lead to host recovery following severe pneumonia (56). In this study, we performed serial sampling of the alveolar spaces of patients with severe pneumonia to test the null hypothesis that dynamic pulmonary T cell responses are similar between causes of pneumonia (57).…”
Section: Discussionmentioning
confidence: 99%
“…Successful pulmonary immune responses to acute infection coordinate innate and adaptive immune events that lead to host recovery following severe pneumonia (56). In this study, we performed serial sampling of the alveolar spaces of patients with severe pneumonia to test the null hypothesis that dynamic pulmonary T cell responses are similar between causes of pneumonia (57).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic, generations of influenza epidemics and pandemics, and the rise of multidrug-resistant bacterial pneumonia have increased awareness of the burden of acute respiratory infections (1,2). Even before the COVID-19 pandemic, pneumonia due to a broad spectrum of viral and bacterial pathogens caused almost 80% of deaths from infection in the United States (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the mortality rate of Gram-negative bacterial pneumonia is still significant even when the optimal antibiotic therapy is provided. 9 Therefore, comprehensive management targeting both patients and pathogens is crucial. This implies that it is necessary to pay attention to the clinical characteristics and risk factors of bacteremic pneumonia caused by these bacteria.…”
Section: Introductionmentioning
confidence: 99%